First Report of Magnetic Resonance Imaging in Patients with Implanted InterStim Twin (model 7427T) Sacral Nerve Stimulator - Heidler, Stefan; Lusuardi, Lukas; Dietersdorfer, Franz (Urology Journal, 2020)
Purpose: To detect possible effects of magnetic resonance imaging (MRI) scans on the function of an InterStim Twin sacral nerve stimulation (SNS) device and on patient’s health. There is no authorization for MRI scans in InterStim Twin SNS at all. Material and Methods: 10 patients with Interstim Twin sacral nerve stimulator implants underwent a singular MRI scan. Before the MRI was performed, the SNS device function was evaluated and the device was deactivated be the implanting urologist. A continuous monitoring took place during MRI procedure. Micturition-time chart pre- and post MRI procedures were conducted. After the MRI session was completed, the implanted device was examined once more and reactivated, function then was evaluated. Results: A total of 10 patients required MRI examinations in 8 different body regions. No patient reported pain or discomfort during and after the MRI scan. After reactivation of the InterStim Twin device following the MRI, impedances and stimulation amplitude, micturition frequency, urgency, and incontinence episodes remained stable. No significant differences between pre- and post MRI were found (p>0.05). Conclusion: This is the first report of patients successfully undergoing a MRI scan despite a previously implanted Interstim Twin sacral nerve stimulator. No negative effect of SNS function or negative side effects for the patients were observed.